Determination of the abortifacient activity of the aqueous extract of Phytolacca dodecandra (L’Her) leaf in Wistar rats - Namulindwa, Angella; Nkwangu, David; Oloro, Joseph (African Journal of Pharmacy and Pharmacology, 2015)
Throughout history women have tried to control their fertility using herbal remedies; traditionally Phytolacca dodecandra leaves have been used as an abortifacient. The objective of this study was to determine the abortifacient activity of the aqueous extract of P. dodecandra leaf in Wistar rats. Hundred grams of shaded dried powdered leaves were soaked in 0.5 L of cold water, and using cold maceration, an aqueous extract was obtained. Acute toxicity was carried out using Lorke’s method. The abortifacient activity of the plant extract was tested using a modified method. Thirty pregnant rats were randomly distributed into five groups each consisting of 6 rats and were treated. The percentage number of rats that aborted per treated group was compared with those of the controls. Preliminary phytochemical screening of the extract revealed the presence of alkaloids, tannins, phenolics, steroids and triterpenoids. Toxicity signs such as reduced appetite, sleepiness, shivering and excessive urination were observed at a dose of 2048 mg/kg; however, no deaths were observed. In the groups in which 125 and 250 mg/kg of P. dodecandra extract was administered, 83.3% of the rats aborted, and in the group in which 500 mg/kg was administered, 100% of the rats aborted. This study has substantiated the abortifacient activity of the aqueous extract of P. dodecandra leaves which may be attributed to the phytochemicals.
Keywords: Abortifacient; Phytochemical screening; Acute toxicity; Phytolacca dodecandra